2008
DOI: 10.1111/j.1748-121x.2007.00071.x
|View full text |Cite
|
Sign up to set email alerts
|

The nature of the FSA policy of rule use: a critical overview

Abstract: The function and effectiveness of legal rules as instruments of social organisation have become an important focus of attention for those interested in financial architecture. This paper offers a critical overview of the policy of rule use of the Financial Services Authority (FSA) in the UK and considers the background of this policy, its nature and some problems pertaining to its implementation. The aim is twofold: first, to describe how current policy trends interact with and shape the FSA's policy of rule u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Ham and Alberti 2002) or finance (e.g. Georgosouli 2008). Yet, even if self‐regulation is well established in many spheres, it is much less visible in what are perceived to be ‘high‐technology’ industries, especially when there are obvious safety concerns, such as in aviation and nuclear power 17 .…”
Section: Bureaucratic Visionsmentioning
confidence: 99%
“…Ham and Alberti 2002) or finance (e.g. Georgosouli 2008). Yet, even if self‐regulation is well established in many spheres, it is much less visible in what are perceived to be ‘high‐technology’ industries, especially when there are obvious safety concerns, such as in aviation and nuclear power 17 .…”
Section: Bureaucratic Visionsmentioning
confidence: 99%
“…Whilst this approach, "both relies on and reinforces the image of the self-observing, responsible organization" 54 it also entails the maintenance of a costly communications network that may further trigger conditions of regulatory capture. 55 The purposive objectives and outcome-oriented approach of the principles-based regulation relies on conversational elements but these require difficult, expensive networks and may involve varying interpretive communities. Some have suggested that the FSA takes a more pro-industry approach, willing to tolerate behaviour harmful to investors rather than scare off business through increased regulatory costs.…”
Section: W W Bratton "Enron Sarbanes-oxley and Accounting: Rules Versus Principles Versus Rents" (2003) 48mentioning
confidence: 99%
“…321 The rulebook has been described by one academic as "conspicuously principles based". 322 What is clear is that the PRA is to replace the six principles for business used by the FSA with nine fundamental principles. 323 Rule 1, 324 that a firm must conduct its affairs with integrity is very similar to the previous rule used by the FSA.…”
Section: ] 9(2) Lfmr 130-144 At 144mentioning
confidence: 99%